Testing out contractual incompleteness : evidence from soccer - Oriol Carbonell-Nicolau; Diego Comin (Rutgers University, Department of Economics, 2005)
The theory of incomplete contracting is rival to that of complete contracting as a frame of reference to understand contractual relationships. Both approaches rest upon diametrically opposed postulates and lead to very different policy conclusions. From a theoretical viewpoint, scrutiny of the postulates has revealed that both frameworks are reasonable. This paper designs and implements an empirical test to discern whether contracts are complete or incomplete. We analyze a problem where the parties? inability to commit not to renegotiate inefficiencies is sufficient for contractual incompleteness. We study optimal contracts with and without commitment and derive an exclusion restriction that is useful to identify the relevant commitment scenario. The empirical analysis takes advantage of a data set from Spanish soccer player contracts. Our test rejects the commitment hypothesis, which entails the acceptance of the existence of contractual incompleteness in the data. We argue that our conclusions should hold a fortiori in many other economic environments.
Keywords: L14; 330; incomplete contract; optimal contract; commitment; renegotiation; Unvollständiger Vertrag; Fußballsport; Schätzung; Spanien